Rod Ejection and Drop Accident Analysis of Aqueous Homogeneous Solution Reactor - Wang, Kunpeng; Xu, Chao; Li, Congxin; Liu, Yusheng; Jing, Jianping; Wu, Hongchun (Frontiers in Energy Research, 2019)
Aqueous Homogeneous Solution Reactor concept has been proposed for producing medical isotopes(Medical Isotope Production Reactor-MIPR). However, there are several difficulties in transient calculation of aqueous homogeneous solution reactors. First, there are no assemblies in the core which is different from the traditional reactor core. Second, the operation of aqueous solution reactor at a power of 200kW will generate radiolytic-gas bubbles. The void volume created by these bubbles in the solution core will introduce a strong negative reactivity feedback. Third, the complex structure of the coolant pipes immersed in fuel solution requires unstructured neutron diffusion calculation methods. Therefore, analytic basis functions expansion nodal method for arbitrary triangular-z node is established to solve the complex structure geometry neutron diffusion equation. Based on this, a software named TABFEN-K has been developed to solve the three-dimensional space-time neutron kinetic equations. Then，TABFEN-K code is used for typical accident analysis of a solution reactor. A simplified geometry model, bubbles generation model , thermal conduction model and and cross section feedback model are given in this paper. A software called TABFEN-MIPR is developed and used for the simulations of the control rod ejection and drop. The same characteristics in the transient process with the results from literatures are obtained.